Perancangan Buku Refrensi Seni Tari Bedhaya Ketawang dengan Menggunakan Teknik Digital Watercolour Illustration Kepada Remaja Guna Melestarikan Budaya Bangsa - Prasetyo, Dimas; Martono, Siswo; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2017)
Bedhaya Ketawang is a traditional dance which has existed since the Kingdom of Mataram, and it is one of the cultures in Indonesia. Bedhaya Ketawang is a sacred dance for predecessors, from the previous kings to the future ones. However, people usually misinterpret the meaning of Bedhaya Ketawang as time goes by. Therefore, a research to create a reference book about Bedhaya Ketawang as a part of history of culture which should be protected. The technique of collecting the data used is through observation, interview, and the study of literature, the study of competitor, and documentation. Each data collected has an important role to the emerged case on designing the reference book of Bedhaya Ketawang using the technique of Digital Watercolour, Illustration for teenagers around 18 to 21 years old as cultural observation efforts, so it requires a lot of accurate data which the result can be responsible. The data is used to find out the initial concept of designing the reference book of Bedhaya Ketawang.The result of the reference book of Bedhaya Ketawang and media implementation has had the elements which are informative from the background of the art to the meanings in the aspects of Bedhaya Ketawang. Based on the concept, the keyword used is Supportive which supposed to be the media reference that can get the positive responses for audiences, which are teenagers from 18 to 21 years old.